Functional and physico-chemical properties of flours and starches of African rice cultivars - Falade, K.O.; Semon, M.; Fadairo, O.S.; Oladunjoye, A.O.; Orou, K.K. (Elsevier, 2014)
Functional, physico-chemical properties and FTIR analysis of flours and starches of two African rice cultivars (Transgressive Segregants TGS 3 and TGS 25) were investigated. The TGS 3 showed higher 1000 kernel grain weight (29.55 g), dockage (1.00 g), immature grain (1.97 g), thickness (2.10 mm), chalkiness (11.17%) and damaged grain (0.70%). However, the TGS 25 showed higher head rice yield (51.11%), milling degree (9.60%), length (6.88 mm) and elongation ratio (3.64). Also, the TGS 25 showed higher alkaline spread value (6.67), amylose content (30.81%), uncooked (7.15 mm) and cooked (10.17 mm) rice length. The WAC (2.77 g/mL) and OAC (1.08 g/mL) of TGS 25 flours were higher than TGS 3. The L value of TGS 25 flour (92.13) and starch (97.88) were higher than those of TGS 3. The TGS 3 flour and starch showed higher peak, breakdown and peak times of 4308 and 3531 cP, 2200 and 1947 cP, 5.43 and 4.60 min, respectively. The TGS 25 (85.67 ° C) starch showed significantly higher boiling point than the TGS 3 (81.33 ° C). Pasting temperatures of TGS 3 and TGS 25 starches were 78.65 and 78.75 °C, respectively. Cyclodextrin (A and B) and L (−) glucose were detected in the starch and flour of TGS 25 but were present in TGS 3 starch but absent in its flour.